Wonderwall - Alandy Dy, Andrea Leslie C. (Animo Repository, 2021)
Wonderwall is a 20-minute slice of life/light drama short film set during the pandemic, about a pianist who finds solace in companionship through music when she hears a piano melody being played on the other side of her wall. The short film features the effects of the COVID-19 pandemic on oneself and one’s well-being, highlighting the themes of loneliness, isolation, and demotivation. More than this, the film reinforces the idea of music being a universal language that can connect people together, and how music in itself is a form of healing. Wonderwall also features an original music composition as the featured piece in the film. This Production Book contains all of the necessary components and documents needed for the proposed feature film. Each component of this Production Book is a creative output which the proponents produced for their film concept, and the proponents followed a strict methodology and schedule in order to produce the book. The proponents prepared the files needed such as the sequence treatment, screenplay, and shooting schedules, researched and canvassed on possible shooting location, equipment and materials/props needed to come up with their proposed budget, and designed and prepared the film posters and a storyboard for the film’s trailer among other production preparations. The proponents also commissioned the film’s original piece from a local composer who provided the sheet music and an audio file of the original composition with the knowledge and consent of their mentor. Preparation for the Production Book began on July 1, 2021 and formally concluded on December 17, 2021. Wonderwall is conceptualized and developed, and its Production Book and it’s individual requirements are prepared and compiled by the three proponents with the exception of the original composition piece. The posters are photographs which were taken by one of the proponents in her own house and utilized Adobe Photoshop to add the poster details. Each collateral has been thoroughly checked and approved by the proponents’ mentor.